2011
DOI: 10.1097/dbp.0b013e3182142fbd
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Race on Participation in Part C Early Intervention Services

Abstract: Objective To quantify racial differences in receipt of early intervention (EI) services among children ages birth to three. Methods We conducted multivariable analyses of a nationally representative sample of children eligible for EI services using data from the Early Child Longitudinal Study, Birth Cohort. Birthweight <1000 grams, genetic and medical conditions associated with developmental delay, or low scores on a standardized measure of developmental performance defined EI eligibility. Receipt of EI serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…This varies from previous reports of race and insurance type impacting access to early intervention and is an encouraging finding. 11,12 We found that children referred for diagnostic ASD evaluation were receiving a mixture of both federally funded programing and privately obtained therapies. Among our sample, almost 70% of children received services under the Individuals with Disabilities Education Act (Part C and Part B).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This varies from previous reports of race and insurance type impacting access to early intervention and is an encouraging finding. 11,12 We found that children referred for diagnostic ASD evaluation were receiving a mixture of both federally funded programing and privately obtained therapies. Among our sample, almost 70% of children received services under the Individuals with Disabilities Education Act (Part C and Part B).…”
Section: Discussionmentioning
confidence: 98%
“…For example, black children at 24 months of age are 5 times less likely to receive early intervention services than white children. 11 Furthermore, utilization of Part C services has also been reported as higher among children with Medicaid. 12 Despite such disparities, recent outcome reports have shown that 71% of all Part C Infant and Toddler Program participants less than 3 years of age have greater than expected growth in knowledge and skills, and 52% of these participants exit the early intervention program with development within age-appropriate limits.…”
mentioning
confidence: 99%
“…Parents from ethnic minority backgrounds may report different levels of interest in interventions that focus on building parenting skills when compared to parents of Caucasian background (Calzada et al 2012), and perhaps because of this, they are less likely to engage in parenting programs (Sanders and Kirby 2012). Racial disparities also exist within other early intervention programs for children with developmental delays (Feinberg et al 2011). Identifying parental preference that may vary across racial/ethnic groups can help understand how certain components of early childhood programs may influence racial/ ethnic minority groups' participation.…”
Section: Parent Race/ethnicitymentioning
confidence: 89%
“…17,25,26 Wang et al 20 reported higher EI enrollment among children with birth weights ,1000 g who were receiving public insurance. Results from our regression analyses also showed that EI referrals were positively associated with public insurance.…”
Section: Discussionmentioning
confidence: 99%